Numerical investigation of rainfall intensity and duration control of rainfall-induced landslide at a specific slope using slope case histories and actual rainfall records - LIU, Xin; WANG, Yu; LEUNG, Anthony Kwan (Bulletin of engineering geology and the environment, 2023)
Rainfall is a major triggering factor for landslide hazards in many regions. The relationship between rainfall characteristics and slope stability is of great importance for mitigating landslide risks. Some recent studies showed that there is a threshold curve of rainfall intensity and duration for a specific slope and that landslides are expected to occur when the rainfall intensity and duration imposed on the slope exceed the threshold curve. These curves offer a convenient way to predict rainfall-induced landslides at a specific slope and provide insights into the slope’s rainfall intensity-duration control of landslides. However, the development of the abovementioned threshold curves in the previous studies was limited to some special slope conditions, such as infinite slopes with a shallow planar failure mode, and contained assumptions inconsistent with field observations, such as fully saturated soil at slope failure. This study aims to address these limitations and assumptions and numerically investigate the rainfall intensity-duration control of rainfall-induced landslides at a specific slope using real slope case histories and actual rainfall records. A generalized procedure is proposed to develop an explicit relationship between rainfall intensity and duration at a specific slope, which is referred to as critical rainfall pattern curve (CRPC). The slope-specific CRPC from different slope case histories can be reasonably fitted by a power function with an R 2 value of 0.988 – 1.000. The CRPCs are consistent with the actual rainfall records and slope failures observed. CRPC provides a simple but effective tool for slope-specific landslide prediction and risk assessment.